2021
DOI: 10.1177/1523422320982933
|View full text |Cite
|
Sign up to set email alerts
|

Not Your Parents’ Organization? Human Resource Development Practices for Sustainable Flex Work Environments

Abstract: The Problem. Everything we know and understand about flexible work arrangements (FWAs) revolves around extant research exploring the effects and effectiveness of FWAs based on samples in which organizations and/or employees freely adopted their use. In a post COVID-19 world, organizations implemented FWAs and employees who may not have been prepared for or desired such arrangements. This has resulted in implementing FWAs in situations where the job, culture, or person does not “support” FWAs. The Solution. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 62 publications
0
19
0
1
Order By: Relevance
“…Telework that involves substantial job autonomy can improve work-life balance and thereby reduce the incidence of burnout [62]. The issues of job autonomy and control, being central to the promotion of work-life balance by telework, also appear in other studies [63,64]. Schellhammer et al [65] argue that telework that provides job autonomy and control can be used by employees for primary preventive health care, such as ensuring sufficient sleep or breaks, or setting time aside when emails are not read.…”
Section: Links Between Telework and The Un Sustainable Development Goalsmentioning
confidence: 94%
See 4 more Smart Citations
“…Telework that involves substantial job autonomy can improve work-life balance and thereby reduce the incidence of burnout [62]. The issues of job autonomy and control, being central to the promotion of work-life balance by telework, also appear in other studies [63,64]. Schellhammer et al [65] argue that telework that provides job autonomy and control can be used by employees for primary preventive health care, such as ensuring sufficient sleep or breaks, or setting time aside when emails are not read.…”
Section: Links Between Telework and The Un Sustainable Development Goalsmentioning
confidence: 94%
“…Population ageing has two problematic economic effects, i.e., shrinkage of the taxpaying labour force, and growth of the elderly in need of caregiving resources. Research in Singapore found that many older individuals who had retired would likely return if employment involving part-time/flexible work in locations close to the home was available [93], and research in the US suggests that older employees value flexible work arrangements more than their younger counterparts [64]. Telework could support these two conditions, particularly for occupations where results are measurable, and hence make developed economies more sustainable.…”
Section: Sdg 8: Decent Work and Economic Growthmentioning
confidence: 99%
See 3 more Smart Citations